THE PERCEPTION OF PALAKKA PEOPLE TOWARD VISITING PETTA BETTA’E GRAVE - La Ode Ismail Ahmad (JICSA : Journal of Islamic Civilization in Southeast Asian, 2018)
This article discusses the perception of Palakka people toward the existence of Petta Betta’e grave. Based on the research, the vast majority of Palakka people believe that spirit of Petta Betta’e still exist and may influence people’s life. This resulted in strongly appreciating and positioning the grave as the noble one among the others. This belief is truly inherited for a number of generations. This tradition illustrates that visiting this grave can further color people’s life before they die. This research aims at providing the people views of point about this historical tradition. This employs qualitative research as an alternative approach to interpret this phenomena. In gaining datas, the author conducts interview, observation and document collection. The research suggests that through strong education in terms of religious understanding, Palakka people will realize the importance of remembering the death people especially their heritage.